The Philippine indigenous cultural communities proposed enrichment instructional materials for secondary social studies - Laboga, Buenaventura Lagarde 1951-
This study explored the integration of the study of Philippine indigenous cultural communities into the secondary social studies curriculum by utilizing the multicultural approach. It sought to answer the major question of what teaching exemplars about the Philippine indigenous cultural communities could be prepared to enrich the background knowledge of social studies teachers in the secondary school.